Peran Guru Bimbingan Dan Konseling Dalam Meningkatkan Motivasi Belajar Peserta Didik Dalam Menghadapi Ujian Nasional Kelas Xi (Studi Kasus di SMAN 2 Kota Tegal): The Role Of Guidance And Counseling In Improving Students 'Learning Motivation In Facing The Class XI National Exam (Case Study In SMAN 2 Kota Tegal) - Sesya Diaz Mumpuni (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2018)
This study aims to determine the activities of guidance and counselling, as well as to help increase knowledge in learning motivation of students in facing the national exam in class XI of SMA N 2 Kota Tegal by using the teacher's role of guidance and counselling. The approach of this research is the qualitative assessment. The subject of this study was the role of the leadership and counselling teacher in Palangka Raya 2 High School. The technique used is the technique of combining data with different methods, namely observation, interviews, and documentation. Analysis of the data used is triangulation. The results of this study indicate that guidance and counselling teachers play an essential role in providing services to students. Through the part of teacher guidance and counselling, it can motivate the eleventh-grade students of SMA N 2 Kota Tegal to be even better than before. The importance of the role of guidance and counselling teachers in schools is one way to motivate or provide support and encouragement to students, by showing students things that are not right or that must be left behind and ask them to do things that should be done correctly, as well as guidance and counselling teachers are very instrumental as motivators and as mentors to motivate students of class XI SMA N 2 Tegal City.